UPAYA GURU PAI DALAM MENINGKATKAN KOMPETENSI BELAJAR SISWA PADA KURIKULUM MERDEKA DI SMAN 1 TAMBUN SELATAN - Mulyadi, Acep; Rizki Gunawan Hsb, Akmal; Lubis, Rabiannur; Nuraini, Zahra (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This thesis research has two objectives: the first objective is to find out the efforts of PAI teachers in improving student learning competence in the independent curriculum at SMAN 1 Tambun Selatan, and the second objective is to find out the obstacles for PAI teachers in improving student learning competency in the independent curriculum in SMAN 1 Tambun Selatan. This research uses qualitative research methods, and this type uses descriptive observation through phenomena. It is also carried out using interview techniques by interviewing two PAI teachers and two class XI students, then analyzing the interviews by researchers with objective data and facts, which were taken from the two teachers and explained clearly and objectively. The results of this thesis research are that a PAI teacher's efforts to improve student's learning competence in the independent curriculum, namely before carrying out learning activities or before the teacher delivers material, the teacher carries out a test in reading the Al-Qur'an, then gives a test regarding knowledge of PAI material, so that the teacher can carry out learning activities according to the capacity of his students. The teacher provides inclusive guidance to his students before carrying out learning. Furthermore, the obstacles are a lack of student motivation, limited time, and a lack of learning methods.